Protection against Exposure Due to Radon Indoors and Gamma Radiation from Construction Materials - Methods of Prevention and Mitigation - IAEA (IAEA, 2021)
This publication presents a review of technical solutions providing both corrective actions and preventive measures to reduce the ingress of radon indoors. A description of methods, design and implementation of measures to reduce ingress of radon into buildings, and of the materials and equipment used in these solutions are included. The publication also presents methods for measuring gamma radiation from radionuclides in building and construction materials and for methods of reducing exposure due to this gamma radiation. Aimed primarily at building and construction professionals designing and installing radon preventive and mitigation measures, this publication will also be a useful resource for national authorities responsible for the development of national building codes and implementation of national radon action plans.
Description based upon print version of record.
Keywords: Gamma rays.; elektronické knihy; electronic books